Combinatorial protective effect of Cinnamomum verum and Stingless Bee Honey against oxidative stress in isoproterenol-induced cardiotoxicity in Wistar rats - Arul Mozhi Padmanabhan; Victor Arokia Doss (Clinical Phytoscience)
Abstract Background Cardiac hypertrophy (CH) is a prevalent consequence of cardiovascular disease, necessitating treatment with synthetic medications that often have adverse effects. Natural products, like Cinnamomum verum (CV) and Stingless Bee Honey (SBH), rich in phenolic compounds, hold promise as safer alternatives. In this study, we investigated the potential cardioprotective effects of CV bark and honey produced by Stingless bee in male Wistar rats. In a 7-day controlled study, rats were randomly assigned into seven treatment groups, receiving either saline (Group I), isoproterenol (ISO) (Group II) or ISO combined with drug interventions of Losartan (Group III), CV (Group IV) and SBH (Group V) along with several combined regimens (Group VI & VII). Biochemical assays were conducted to measure antioxidant enzyme activities (Superoxide Dismutase, Catalase, Glutathione Peroxidase), non-enzymatic antioxidants (Vitamin C, Vitamin E, Reduced Glutathione), inflammatory markers, and oxidative stress levels. Histopathological analysis was also performed. stress markers in cardiac tissues, shedding light on potential therapeutic interventions. Results ISO induces myocardial oxidative stress, characterized by reduced antioxidants, increased oxidative stress and inflammatory markers with elevated collagen content. Our results show that co-administration of CV + SBH effectively attenuated ISO-induced myocardial oxidative stress, outperforming individual CV or SBH administration in restoring antioxidant levels and normalizing oxidative stress and inflammatory markers. Conclusions The results from this study underscore the importance of advancing research on the combination of CV and SBH, which hold significant promise as synergistic therapeutic agents in the treatment of complex diseases, potentially informing future healthcare policies and clinical practices.